The learning curve for lumbar discectomy in unilateral biportal endoscopic spine surgery using the cumulative summation method - Takaki Yoshimizu; Sanshiro Saito; Teruaki Miyake; Tetsutaro Mizuno; Ushio Nosaka; Keisuke Ishii; Mizuki Watanabe; Kanji Sasaki (Journal of Orthopaedic Surgery and Research)
Abstract Background Unilateral biportal endoscopy (UBE) is gaining popularity owing to its versatility as a spinal endoscopic procedure. However, the general value of the learning curve for discectomy by UBE is unknown. This retrospective study aimed to determine the learning curve of UBE for lumbar discectomy using a cumulative summation (CUSUM) method. We examined the learning curves of four surgeons at an institution and factors that shortened the learning curves. Methods The study included 200 patients (mean age 44.2 years) who underwent lumbar discectomy by UBE at our hospital and four male orthopedic surgeons who had performed 50 UBE discectomies. An approximate curve using the CUSUM method was created using the mean operative time for each case as the target. All surgeons had performed lumbar discectomy and over 200 spinal surgeries before inducing UBE. Surgeon A received specialized training in shoulder arthroscopic surgery. The surgical times before and after the curve reached its maximum value were compared; a point of significant difference was defined as case to proficiency. Results The mean operative times for surgeons A, B, C, and D were 48, 66, 90, and 87 min, respectively. The approximate curves obtained using the CUSUM method had maxima at x = 22, 20, 27, and 13. The operating times of Surgeons A and B showed significant differences before and after the maxima (59 vs. 39 and 75 vs. 60), whereas those of Surgeons C and D did not (96 vs. 84 and 95 vs. 85). Conclusions UBE is generally considered to have a steep learning curve; in this study, the learning curve differed depending on the surgeon. The surgeon with the best learning curve was trained as an arthroscopic surgeon. Coordination for endoscopic surgery influenced the learning curve compared to the experience with spine surgery.